Clinical presentation and outcome of children with central diabetes insipidus associated with a self‐limited or transient pituitary stalk thickening, diagnosed as infundibuloneurohypophysitis. (5th June 2017) - Schaefers, J.; Cools, M.; De Waele, K.; Gies, I.; Beauloye, V.; Lysy, P.; Francois, I.; Beckers, D.; De Schepper, J.
Summary: Objective: Despite lymphocytic or autoimmune infundibuloneurohypophysitis (INH) is an increasingly recognized aetiology in children with central diabetes insipidus (CDI); clinical data on epidemiology (clinical evolution, predisposing factors, complications), diagnosis and management of this entity are limited and mostly based on published case reports. The aim of this study was to gain a broader insight in the natural history of this disease by analysing the clinical presentation, radiological pituitary stalk changes, associated autoimmunity and hormonal deficiencies in children with CDI and a self‐limiting or transient stalk thickening (ST), diagnosed as autoimmune infundibuloneurohypophysitis, during the last 15 years in four Belgian university hospitals. Design and Patients: The medical files of nine CDI patients with a ST at initial presentation and no signs of Langerhans cell histiocytosis or germinoma at presentation and/or during follow‐up of more than 1.5 years were reviewed. Results: Age at presentation ranged from 3 to 14 years. Two patients had a positive family history of autoimmunity. Three children presented with associated growth failure, two with nausea and one with long‐standing headache. Median maximal diameter of the stalk was 4.6 mm (2.7‐10 mm). Four patients had extra‐pituitary brain anomalies, such as cysts. One patient had central hypothyroidism, and another had a partial growth hormone deficiency at diagnosis. Within a mean follow‐up of 5.4 (1.5‐15) years, stalk thickening remained unchanged in two patients, regressed in one and normalized in six children. CDI remained in all, while additional pituitary hormone deficiencies developed in only one patient. Conclusions: In this series of children INH with CDI as initial presentation, CDI was permanent and infrequently associated with anterior pituitary hormone deficiencies, despite a frequent association with nonstalk cerebral lesions.